If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 46 = 2x Solving 46 = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 46 + -2x = 2x + -2x Combine like terms: 2x + -2x = 0 46 + -2x = 0 Add '-46' to each side of the equation. 46 + -46 + -2x = 0 + -46 Combine like terms: 46 + -46 = 0 0 + -2x = 0 + -46 -2x = 0 + -46 Combine like terms: 0 + -46 = -46 -2x = -46 Divide each side by '-2'. x = 23 Simplifying x = 23
| 5/2(7x-15)+13/2x-3/2 | | K^2-9k+10=10 | | sin(x)cos(2x)+cos(x)sin(2x)=0 | | z^2=63 | | 4x+4y=-20 | | .237=x^5 | | -5x^2-3x=-5 | | 1/2-x/3+3=5x/6 | | X(X+1)=X(X+3)-2X | | 12x-3=9y | | 6/3x-5=6/2x+3 | | 2(x-4)=3(x-9) | | x+.4(5)=.5(x+5) | | 5/6x-x/18-3/4x=7/12-2/9x+2/3 | | -4-(3/4x)=17 | | (3-X)(9-X)=(9-X)(11-X) | | -2+8x+12=4(2x+3) | | 7x-144=2x-9 | | 6x+5=5(x) | | 8(x-1)=3(2x+2) | | x+2=4y | | 3/8x+2-4/5x1+3/10x+3/2 | | 8/15+1/15 | | x+2.8=.7x+4.9 | | k+q=a | | A=K(n+N)forN | | -2-6x=8-6x | | k+q=aforq | | 80=2(lw+hw+hl) | | 840/1575 | | 3(x+6)=5x | | 2x+2=5y+7 |